Utilization of the Industrial Revolution Era 4.0 as an Effort to Support Student Character Education - Anindia Nur Amalia; M. Ilham Karisma (Proceedings of The ICECRS, 2020)
In the 21st century the world of education is undergoing various changes in the educational paradigm that places humans as a whole, human resources that can provide policy direction in laying the framework for development and utilizing the era of the industrial revolution 4.0 in the sphere of education. The expected learning process is to be able to develop a variety of potential learners as a whole in an integrated manner, therefore in the provision of material or the learning process everything must be able to actualize efforts to shape student character through personality development. The existence of character education for the sake of facing and utilizing the era of the industrial revolution 4.0 can form students who have identity. However, in shaping the identity, several strategies are needed to support the identity of students that are adapted to the era of the industrial revolution 4.0 at this time. For example, by creating an innovation called the "Expression Room" which is used as a potential container for students. Character education must also be able to equip students with competence in the ability to communicate, organize, solve problems, be independent, cooperate, and be ethical.